ANALISIS PERTUMBUHAN EKONOMI DAN KEUNGGULAN SEKTOR PERTANIAN INDONESIA - Nur Fitriana; Dwidjono Hadi Darwanto; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2008)
The study aims: (1) to measure the growth rate of economic sector based on Gross Domestic Product; (2) to determine contribution of economic sector to GDP; (3) to measure contribution trend of economic sector of GDP and to determine basic sectors inprovinces of Indonesia. The data used is secondary datafrom Badan Pusat Statistik, i.e. Gross Regional Domestic Product and Gross Domestic Product according with 1993 constant price. Data included overall provinces in Indonesia among 19842003. Table analysis, Location Quotient, shift-share, and Klassen Typology were used to analyze. The results are: (1) growth rate o/GDP is positively fluctuated, except at 1998 due to economic crisis; (2) contribution ofagricultural sector; mining and quarrying sector; and services sector weredecreased Contribution of manufacturing industries sector; electricity, gasand water supply sector; trade, restaurant and hotel sector; and transportation and communication sector were increased. Contribution of construction sector and finance and rent of building and business sector werefluctuated; (3) overall sector follow quadratic pattern, exceptfinance, building rent, and business sector that follow linear pattern; (4) agricultural sector was the basic sector in ·26 provinces, except in East Kalimantan, Banten, WestJava and Jakarta.